Metode Small Group Discussion (SGD) Pada Mahârah Qirâ'ah di Madrasah Tsanawiyah - Hudriyah Hudriyah; Robi’atul Hadawiyah; Muhammad Afif Maulidy (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2021)
This article examines the learning process that applies the small group discussion method or abbreviated as SGD. Small group discussion is one of the collaborative learning activities which in this learning aims to maximize the process of cooperation between students in the continuity of the learning process. Some elements emphasized in this method are the social skills of students and groups so that they are active in receiving the material presented and provide opportunities for students to dare to criticize ideas and maintain students' logical thoughts. So with the application of the SGD method, it is expected that motivation and a sense of enthusiasm in student learning can increase, so that students can follow the learning process well which of course makes students not bored when the learning process takes place